Studies on Scaling and Corrosion Characteristics of Ground Water - Gopi, D.; Girija, T.C.; Ramesh, S.; Rajeswari, S. (Asian Journal of Chemistry, 2010)
Scale formation and corrosion affect the performance of an open recirculating cooling system, which is considered as an important component in most of the industries. This article deals with the evaluation of scaling and corrosion tendency of groundwater samples collected from various locations in Chennai city. The evaluating procedures include determination of water quality parameters like pH, alkalinity, Total dissolved solids (TDS) and hardness. This article also deals with the evaluation of scale and corrosion inhibition efficiency of some of the inhibitors.